2021
DOI: 10.1111/ijfs.15092
|View full text |Cite
|
Sign up to set email alerts
|

Application of whey of Mozzarella di Bufala Campana fermented by lactic acid bacteria as a bread biopreservative agent

Abstract: A total of nine isolated lactic acid bacteria (LAB) from tomato and sourdough with antifungal activity were employed to revaluate the whey of Mozzarella di Bufala through the fermentation process for 72 h at 37°C. Then, the fermented whey (BWF) was characterised and used as biopreservative in bread formulation. L. plantarum TR7 and L. plantarum TR2 strains showed average lactic acid concentration in BWF of 13.8 g L À1 . Also, the bread volatile organic compounds (VOC) analysis showed an increase in hexanal, be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The worldwide production and consumption of buffalo milk have significantly increased since 2005, generating more than 127 million tonnes of milk in 2018 (Zicarelli, 2020). As one of the techniques for preserving this raw material, cheese production stands out, but it generates a considerable volume of cheese whey as a co‐product (Luz et al ., 2021). Cheese whey proteins have high levels of essential amino acids, providing a high biological value.…”
Section: Introductionmentioning
confidence: 99%
“…The worldwide production and consumption of buffalo milk have significantly increased since 2005, generating more than 127 million tonnes of milk in 2018 (Zicarelli, 2020). As one of the techniques for preserving this raw material, cheese production stands out, but it generates a considerable volume of cheese whey as a co‐product (Luz et al ., 2021). Cheese whey proteins have high levels of essential amino acids, providing a high biological value.…”
Section: Introductionmentioning
confidence: 99%
“…The results from Ryan et al (2008) showed that the combination of sourdough and 0.1% calcium propionate effectively extended the shelf-life of bread, which was similar to bread supplemented with 0.3% calcium propionate alone. Luz et al (2021) also found that relative to bread supplemented with 0.3% calcium propionate and 3 g/kg lactic acid, bread supplemented with 25 ml Lactiplantibacillus plantarum TR7 fermented whey had its shelf-life extended by 1 day, while the shelf-life of bread supplemented with 50 ml fermented whey was extended by 2 days. Ryan et al (2011) also similarly found that 0.3% calcium propionate-supplemented bread had weaker antiseptic effects than bread fermented by L. amylovorus DSM 19280.…”
Section: Application Of Antifungal Lab In Bakery Productsmentioning
confidence: 89%
“…Volatile Organic Compounds (VOCs) emitted by the bacteria after fermentation in MRSb and MB10 media were determined by head-space solid phase microextraction (HS-SPME) technique and subsequent analysis in a gas chromatograph coupled to a mass spectrometer (GC-MS) following the methodology of Luz et al [ 32 ] with minor modifications.…”
Section: Methodsmentioning
confidence: 99%